COMPLEMENTARY FINDINGS ON THE ANTIMALARIAL ACTIVITY AND TOXICITY OF METHYLENE BLUE. - GARAVITO, Giovanny; BERTANI, Stephane; DEHARO, Eric (Vitae, 2009)
Methilene blue was reported as the first synthetic antimalarial by Ehrlich in 1881. It is currently no longer used for that purpose but it should be reconsidered since new economic alternatives are urgently needed in the arsenal of antimalarial drugs. The antimalarial activity of methylene blue is investigated here in vivo against rodent malaria parasites. 15 mg/kg daily dose of methylene blue inhibits 50% of the erythrocytic parasite growth of Plasmodium berghei and P. yoelii nigeriensis, while on hepatic stages of P. yoelii yoelii is almost inactive. In cell culture experiments with the lymphoblast-like BJAB cells line, it is 20 times more cytotoxic than chloroquine. Nevertheless, methylene blue shows a similar selectivity index as chloroquine against strains of different level of sensitivity of P. falciparum original from different geographical areas.